Arabidopsis thaliana plants acclimated to low dose rates of ultraviolet B radiation show specific changes in morphology and gene expression in the absence of stress symptoms - Hectors, Kathleen (The New phytologist, 2007)
Ultraviolet B (UV-B) acclimation comprises complex and poorly understood changes in plant metabolism. The effects of chronic and ecologically relevant UV-B dose rates on Arabidopsis thaliana were determined. The UV-B acclimation process was studied by measuring radiation effects on morphology, physiology, biochemistry and gene expression. Chronic UV-B radiation did not affect photosynthesis or the expression of stress responsive genes, which indicated that the UV-acclimated plants were not stressed. UV-induced morphological changes in acclimated plants included decreased rosette diameter, decreased inflorescence height and increased numbers of flowering stems, indicating that chronic UV-B treatment caused a redistribution rather than a cessation of growth. Gene expression profiling indicated that UV-induced morphogenesis was associated with subtle changes in phytohormone (auxins, brassinosteroids and gibberellins) homeostasis and the cell wall. Based on the comparison of gene expression profiles, it is concluded that acclimation to low, chronic dose rates of UV-B is distinct from that to acute, stress-inducing UV-B dose rates. Hence, UV-B-induced morphogenesis is functionally uncoupled from stress responses